2020
DOI: 10.1016/j.ijid.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Human Parvovirus 4: A harmless bystander or a pathogen of severe acute respiratory illness

Abstract: Introduction: Severe Acute Respiratory Infection (SARI) is an important cause of morbidity and mortality worldwide, caused by a large number of viral and bacterial agents. PARV4 is a recently identified virus detected in human blood and variety of tissues, but its disease association with SARI could not be established.Objective: In the present case control study, we aim to investigate the association of PARV4 with SARI. Methods: The Nasal and Throat swab (NS/TS) samples of 241 cases and 146 healthy controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Genotype‐2 (formerly known as PARV5) has been identified in European and North American cohorts 2,15 . It was also the predominant strain reported from Asia 2,5 . However, further studies need to be done from different parts of the world for better insight into the genotypic association of human PARV4 with ILI.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype‐2 (formerly known as PARV5) has been identified in European and North American cohorts 2,15 . It was also the predominant strain reported from Asia 2,5 . However, further studies need to be done from different parts of the world for better insight into the genotypic association of human PARV4 with ILI.…”
Section: Discussionmentioning
confidence: 99%
“…The virus has been detected worldwide in plasma and different tissues, and it seems to be transmitted parenterally to hemophiliacs and injection-drug users, but with no clear clinical manifestations (reviewed in [ 14 ]). However, a recent study reported a strong association between PARV4 and individuals showing severe respiratory illness, and its DNA was found in cerebrospinal fluid from two children with encephalitis [ 16 , 17 ]. PARV4 has been assigned to the genus Tetraparvovirus , along with other members infecting pigs, sheep, cattle, yaks, and bats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human parvovirus 4 (PARV4), a virus belonging to the genus Tetraparvovirus was first described in 2005 in plasma from patients with acute viral infection syndrome. It has been classified in three genotypes, and genotype 2 was formerly known as PARV5 [ 5 , 13 , 14 ]. The low genetic diversity between PARV4 genotypes (<3% at the amino acid level) supports that introduction in human populations is likely to have occurred recently [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low genetic diversity between PARV4 genotypes (<3% at the amino acid level) supports that introduction in human populations is likely to have occurred recently [ 15 ]. PARV4 has been detected in blood/plasma samples, autopsy samples, stools, nasopharyngeal swabs, bone marrow and cerebrospinal fluid; the clinical impact of PARV4 infection remains uncertain, but reported disease associations include influenza-like syndrome, encephalitis, worsening of HIV evolution and fetal hydrops; PARV4 association with gastroenteritis remains to be established [ 5 , 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%